The Impact of Ownership Structure on Corporate Social Responsibility Disclosure in Saudi Arabia - Boshnak, Helmi A. (International Journal of Economics and Financial Issues, 2025)
The aim of this study is to examine how different forms of ownership impact Corporate Social Responsibility (CSR) disclosure in Saudi listed firms. The impact of ownership structure on CSR disclosure is modelled by means of an Ordinary Least Square (OLS) regression for 70 listed firms over the period 2016 to 2022, and a Two-Stage Least Squares Method (2SLS) is estimated to tackle any endogeneity issues. Differing ownership structures are captured through investigating government, institutional, family, managerial and foreign ownership, while firm CSR disclosure is measured in terms of environmental CSR and social CSR disclosures. The results reveal that the degree of government, institutional, and foreign ownership are positive drivers of CSR disclosure, while managerial ownership is a negative driver. The findings provide support for both agency theory and stakeholder theory. Further, larger, more established and manufacturing firms engage in greater CSR disclosure generally across the models, while more highly levered firms using more prominent auditors engage more in environmental CSR disclosure alone. The findings have important implications for regulators, policymakers, and managers who wish to enhance CSR. The implications for policymakers are that government, institutional, and foreign ownership should be supported over managerial ownership to improve CSR. The findings suggest that managers should develop more focused intervention mechanisms to match the attitudes of different owners toward CSR. The study may also strengthen the call for a code of CSR reporting consistent with Saudi Vision 2030.